Investigation of ionic-conductive biodegradable electrolyte for organic electrochemical transistors - Tan, Keng Soon (Nanyang Technological University, 2024)
With the rise of the Internet of Things (IoT), flexible and biocompatible electronic devices have garnered increased attention from researchers and industries. Transistors, as fundamental components in electronic circuits, play a crucial role in advancing this area. However, conventional transistors, which predominantly depend on rigid silicon substrates, are unsuitable for flexible and biocompatible applications. Organic electrochemical transistors (OECTs) have emerged as a promising alternative due to their ease of fabrication, high transconductance, and low toxicity. However, most reported OECTs rely on liquid electrolytes, which may evaporate over time, affecting long-term device performance. Solid electrolytes, comprising ionic liquids and polymer matrices, offer potential solutions but may contain toxic components, posing challenges in biocompatible applications. Hence, there is a pressing need to develop new biocompatible solid electrolytes for OECTs to ensure their viability. This project attempted to fabricate a nano cellulose-based OECT that performs similarly to a typical solid OECT but with additional features such as flexibility, biodegradability, and the simplification of the fabrication process. Measurements were carried out to determine the performance of the fabricated nano cellulose-based OECT by comparing it against a typical standard OECT. The results were then analysed to investigate factors that might influence the performance of OECTs.